Thermally-insulated flash sintering. (15th March 2019) - Biesuz, Mattia; Dong, Jian; Fu, Shuai; Liu, Yunlong; Zhang, Haiwen; Zhu, Degui; Hu, Chunfeng; Grasso, Salvatore
Abstract: The use of thermal insulation in flash sintering is proposed in this work. The results show that during conventional flash processes heat losses by radiation accounts for ~90% of the total energy input. Apart from being energy inefficient, heat losses have a negative effect on sample homogeneity. By employing insulating felts or powder beds these losses can significantly reduced while resulting in an improved densification. Analytical calculation, corroborated by experimental results, show an improvement up to 10% of the final density when a thermal insulation was employed. Graphical abstract: Unlabelled Image